Effect of Prices and Promotions on Consumer Loyalty through Gaby Hijab Consumer Satisfaction in Masamba, North Luwu Regency - M.Risal, Muhammad Aqsa, Mahfud Sidiq (International Journal of Advanced Science and Technology, 2020)
This study aims to determine the effect of price and promotion on consumer loyalty mediated by Gaby hijab consumer satisfaction in Masamba, North Luwu Regency. This research is a quantitative study, using primary data. Population determination used in this study were all Gaby hijab consumers in Masamba, North Luwu Regency as many as 150 people. Thus the existing population was taken as the object of study studied and treated as well as a sample of 150 people. The variables in this study were analyzed with the Structural Equation Modeling (SEM) approach, Test Validity, and Test Reliability of the variables that have been set. The results of this study indicate that partially the price variable have a positive but not significant effect on consumer satisfaction, the promotion variable have a positive and significant effect on customer satisfaction, the promotion variable and the price have a positive and significant effect on consumer satisfaction simultaneously, the price variable have a positive and significant effect on loyalty consumers, the promotion variable has a positive and significant effect on customer loyalty, the variable of customer satisfaction have a positive but not significant effect on customer loyalty, the price variable and promotion have a positive and significant effect to customer loyalty that is mediated simultaneously by customer satisfaction. Keywords: price, promotion, consumer satisfaction and consumer loyalty.